Dopaminergic Hyperactivity Accompanied by Hyperlocomotion in C57BL/6J-bgJ/bgJ (beige-J) Mice - Tomohisa Mori; Masahiko Funada; Yuko Tsuda; Jun Maeda; Masashi Uchida; Tsutomu Suzuki (Elsevier, 2014)
Abstract.: Genetic factors affect locomotor activity, which mainly depends on the activation of dopaminergic systems. C57BL/6J-bgJbgJ (beige-J) mice, which exhibit deficiencies in immunological function, show behavioral hyperactivity. The present study was designed to investigate the locomotor activity of beige-J mice accompanied by a change in the dopaminergic system. Beige-J mice showed higher locomotor activity and dopamine turnover, whereas splenectomy reduced this hyperlocomotion and dopamine turnover. These results suggest that beige-J mice could be suitable as an experimental animal model for investigating hyperactivation of the dopaminergic system, and the spleen may contribute to the susceptibility of dopaminergic systems to activation. Keywords:: beige-J mouse, dopamine, splenectomy